CRYOPRESERVATION OF DENDROBIUM SONIA-28 USING AN ALTERNATIVE METHOD OFPVS2 DROPLET FREEZING - Poobathy, Ranjetta; Izwa, Norsyafizatul; Julkifle, Advina L.; Subramaniam, Sreeramanan (Emirates Journal of Food and Agriculture, 2013)
Dendrobium sonia-28, an ornamental orchid in the Malaysian flower industry, is under risk of producing heterozygous progenies. Cryopreservation is a favoured long-term storage method for orchids with propagation problems. The droplet-freezing technique, utilising the principles of vitrification, has emerged as an important technique in the preservation of various plant species. This study was conducted to optimise the droplet-freezing technique for protocorm-like bodies (PLBs) of Dendrobium sonia-28, with viability tests conducted through the 2,3,5-triphenyltetrazolium chloride assay. The best results were obtained when 1-2 mm PLBs were precultured for 24 hours on half-strength Murashige and Skoog (MS) semi-solid medium supplemented with 0.5 M sucrose, placed in a loading solution for 10 minutes and dehydrated in PVS2 at 0°C for 20 minutes, prior to thawing, unloading in 1.2 M sucrose and recovery on semi-solid recovery medium composed of half-strength MS components and 2% sucrose for three weeks.